2014
DOI: 10.1183/09031936.00080913
|View full text |Cite
|
Sign up to set email alerts
|

Club cell 10-kDa protein attenuates airway mucus hypersecretion and inflammation

Abstract: Bacterial lipopolysaccharide (LPS) and interleukin (IL)-13 increase mucus secretion and inflammatory cytokine production in normal human bronchial epithelial (NHBE) cells. We evaluated the effect of club cell 10-kDa protein (CC10), an anti-inflammatory protein produced by epithelial cells, on mucus secretion, cell morphology and inflammatory cytokine production. NHBE cells were cultured at an air-liquid interface with CC10 or vehicle and exposed to LPS on day 14. Mucin MUC5AC, IL-8 and granulocyte-macrophage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 44 publications
0
45
0
Order By: Relevance
“…43,44 Following acute viral infections, transgenic mice deficient in CC16 develop a more severe lung inflammation with increased Th2 cytokine levels, airway reactivity, and mucous production, as well as prolonged viral persistence. 45,46 Reconstitution of CC16 in mice is able to reverse these altered phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Following acute viral infections, transgenic mice deficient in CC16 develop a more severe lung inflammation with increased Th2 cytokine levels, airway reactivity, and mucous production, as well as prolonged viral persistence. 45,46 Reconstitution of CC16 in mice is able to reverse these altered phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…CC16 polymorphism and local deficiency on the one hand, and a decreased number of club cells on the other hand, were reported as features of COPD [8,9], as confirmed by LAUCHO-CONTRERAS et al [10] in the current issue of the European Respiratory Journal. In previous studies, exogenous CC16 showed pharmacological properties that could decrease excess airway inflammation and mucus production in ex vivo models [11][12][13]. However, CC16 has not demonstrated physiological properties, as shown in a prior report on CC16-deficient mice, which were not more susceptible to changes induced by cigarette smoke [14].…”
mentioning
confidence: 90%
“…The study by TOKITA et al [10] adds to the body of evidence showing that CC10, at physiologically relevant concentrations, may contribute to the maintenance of homeostasis in the peripheral airways. Does this also mean that CC10 is a candidate drug for the treatment of inflammatory lung diseases?…”
mentioning
confidence: 96%
“…In this issue of the European Respiratory Journal, TOKITA et al [10] provide evidence that CC10 may also inhibit mucus secretion by lipopolysaccharide-or IL-13-exposed human primary bronchial epithelial cells. They cultured these cells at the air-liquid interface to allow mucociliary differentiation, and showed that CC10 at 20 ng?mL -1 inhibited secretion and mRNA expression of both the mucin MUC5AC and the neutrophil chemoattractant IL-8/CXCL8.…”
mentioning
confidence: 99%